2019
DOI: 10.1051/0004-6361/201935820
|View full text |Cite
|
Sign up to set email alerts
|

Plasmoid-mediated reconnection in solar UV bursts

Abstract: Context. Ultraviolet bursts are transients in the solar atmosphere with an increased impulsive emission in the extreme UV lasting for one to several tens of minutes. They often show spectral profiles indicative of a bi-directional outflow in response to magnetic reconnection. Aims. To understand UV bursts, we study how motions of magnetic elements at the surface can drive the self-consistent formation of a current sheet resulting in plasmoid-mediated reconnection. In particular, we want to study the role of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 57 publications
9
37
0
Order By: Relevance
“…There, following flux emergence the minority polarity cancels with the majority polarity of opposite sign (Chitta et al 2017a). Another recent reconnection modelling shows a similar situation as drawn in our Figure 15, which is found to lead to a bi-directional jet (Peter et al 2019b).…”
Section: Proposed Configuration and Reconnection Of The Magnetic Fielsupporting
confidence: 86%
“…There, following flux emergence the minority polarity cancels with the majority polarity of opposite sign (Chitta et al 2017a). Another recent reconnection modelling shows a similar situation as drawn in our Figure 15, which is found to lead to a bi-directional jet (Peter et al 2019b).…”
Section: Proposed Configuration and Reconnection Of The Magnetic Fielsupporting
confidence: 86%
“…4.1 for discussion. Pontin et al 2013;Cheung et al 2015;Chitta et al 2017b;Peter et al 2019). This is similar to the case discussed in Fig.…”
Section: Magnetic Properties Of Hot Loopssupporting
confidence: 81%
“…Numerical simulations have shown that the magnetic topology that determines the height of reconnection along with the line of sight to the reconnection site play a role in the visibility of these small-scale heating events across the wavelength spectrum (Hansteen et al 2019;Peter et al 2019;Ortiz et al Movie associated to Fig. 5 is available at https:// www.aanda.org 2020; Syntelis & Priest 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, strong emission in the wings of Hα would imply reconnection in the lower atmosphere, whereas bright Mg ii h and k, Si iv 1393.7, 1402.8 Å or even extreme-ultraviolet (EUV) emission would originate in higher layers. Other key signatures such as recurrence, intermittency, and large flow velocities may be caused by the release of fast-moving sequences of magnetic islands (or plasmoids) and jets (e.g., Karpen et al 1995;Shibata & Tanuma 2001;Bhattacharjee et al 2009;Innes et al 2015;Ni et al 2015;Rouppe van der Voort et al 2017;Peter et al 2019), while turbulence has also been shown to potentially play a role in triggering fast reconnection in MFs (e.g., Chitta & Lazarian 2020).…”
Section: Introductionmentioning
confidence: 99%